2009
DOI: 10.1115/1.3066736
|View full text |Cite
|
Sign up to set email alerts
|

Interval Uncertainty Reduction and Single-Disciplinary Sensitivity Analysis With Multi-Objective Optimization

Abstract: Sensitivity analysis has received significant attention in engineering design. While sensitivity analysis methods can be global, taking into account all variations, or local, taking into account small variations, they generally identify which uncertain parameters are most important and to what extent their effect might be on design performance. The extant methods do not, in general, tackle the question of which ranges of parameter uncertainty are most important or how to best allocate Investments to partial un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…This method however did not address the interaction between design parameters, and only the main effect was analyzed. A hybrid approach [26,27] was developed to analyze the sensitivity of parameterized interval variables via multi-objective optimization problems, where the variation of an output with a given interval input was estimated by optimization. The searching procedure for optimization can be computationally expensive for highly nonlinear and coupled systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method however did not address the interaction between design parameters, and only the main effect was analyzed. A hybrid approach [26,27] was developed to analyze the sensitivity of parameterized interval variables via multi-objective optimization problems, where the variation of an output with a given interval input was estimated by optimization. The searching procedure for optimization can be computationally expensive for highly nonlinear and coupled systems.…”
Section: Introductionmentioning
confidence: 99%
“…Different from other interval based SA approaches [25][26][27], our approach considers both the main and interaction effects for feasible design problems with continuous design parameters. Our SA approach for interval-valued variables is global.…”
Section: Introductionmentioning
confidence: 99%
“…Other work has explored the use of target sets to decompose the design space and identify optimal solutions [39]. Further opportunities can be found in robust design, where research has characterized the effect of design variable variations on performance [40] while applying regionalized sensitivity analysis [41] and internal-reduction measures [42].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the authors showed that quality control [18], improved failureprediction models [19,20] can lead to substantial reduction of failure probability of aerospace structures. More recently, Li et al [21] considered systems that have interval uncertainty in their inputs. They developed a multiobjective optimization model to obtain optimal reduction of parameter uncertainty that provide the maximum improvement in system performance with the least amount of investment.…”
mentioning
confidence: 99%